Pengaruh Strategi Pemasaran Digital terhadap Loyalitas Merek melalui Keterlibatan Konsumen Kepuasan Pelanggan dan Kepercayaan Merek pada Platform E-Commerce - Mochammad Ridho; Andi Muh Wahyu Effendy; Nurul Chaerani S Amin; Asrianti Asrianti; Fakhirah Husain (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
The rapid development of the e-commerce ecosystem in Indonesia has encouraged business actors to adopt more integrated, interactive, and customer-oriented digital marketing strategies in order to build sustainable long-term relationships. This study aims to examine the influence of digital marketing strategies on brand loyalty on e-commerce platforms, such as Shopee, Tokopedia, Lazada, and TikTok Shop, by considering consumer engagement, customer satisfaction, and brand trust as mediating mechanisms. Research data were collected through questionnaires distributed to 150 respondents who are active users of e-commerce platforms in Indonesia. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The analysis assessed validity, reliability, path coefficients, R-square values, and mediating effects through the bootstrap technique. The findings of this study are expected to provide theoretical contributions to the development of digital marketing research, as well as practical implications for e-commerce marketing managers in designing digital campaigns that can enhance engagement, increase consumer satisfaction and trust, and ultimately strengthen brand loyalty in a sustainable manner.